Micronutrient fortified yogurt as an incentive in dairy value chains to increase milk deliveries and improve child nutrition - CGIAR Research Program on Policies, Institutions, and Markets (2017)
A micro-nutrient fortified yogurt (MNFY) was developed to increase milk deliveries and improve child nutrition among remote semi-nomadic milk producers in Northern Senegal. Results from the study showed that the MNFY incentive led to increased milk deliveries and improved haemoglobin levels of producer’s children. The processing company that created the MNFY is now planning to scale up the MNFY product to all 12,000 distribution points